2017
DOI: 10.1158/1078-0432.ccr-16-1780
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Sipuleucel-T and Androgen Deprivation Therapy in Men with Hormone-Sensitive Biochemically Recurrent Prostate Cancer: A Phase II Randomized Trial

Abstract: Purpose: STAND, a randomized, phase II, open-label trial (NCT01431391), assessed sequencing of sipuleucel-T (an autologous cellular immunotherapy) with androgen deprivation therapy (ADT) in biochemically recurrent prostate cancer (BRPC) patients at high risk for metastasis.Experimental Design: Men with BRPC following prostatectomy and/or radiotherapy, a PSA doubling time 12 months, and no metastasis were enrolled. Patients were randomized (34/arm) to sipuleucel-T followed by ADT (started 2 weeks after sipuleuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…Studies of the pattern of rise in immunoglobulin levels after SIP-T show a maximal increase 2 weeks after the third infusion of SIP-T, which was continuously maintained without any further augmentation 9. A similar pattern of maximal immunoglobulin rise soon after the third dose of SIP-T without any further subsequent increase was also observed in the STAND trial 10. This pattern of maximal immunoglobulin increase after three cycles of SIP-T has been consistent in all the reported trials.…”
Section: Discussionsupporting
confidence: 52%
“…Studies of the pattern of rise in immunoglobulin levels after SIP-T show a maximal increase 2 weeks after the third infusion of SIP-T, which was continuously maintained without any further augmentation 9. A similar pattern of maximal immunoglobulin rise soon after the third dose of SIP-T without any further subsequent increase was also observed in the STAND trial 10. This pattern of maximal immunoglobulin increase after three cycles of SIP-T has been consistent in all the reported trials.…”
Section: Discussionsupporting
confidence: 52%
“…T-cell responses were assessed by IFNγ ELISPOT and were similar between the groups at all time points except week 6, where there was significantly higher IFNγ production in sip-T→ADT compared to ADT→sip-T (p=0.013). Furthermore, T cell proliferation was 2-fold higher in sip-T→ADT compared to ADT→sip-T (Antonarakis et al 2016b). The authors concluded that the timing of androgen deprivation therapy might affect the efficacy of immunotherapy, and that a preferred sequence would be to use sip-T prior to ADT in this patient population.…”
Section: Androgen Deprivation Combined With Immune-based Treatments –mentioning
confidence: 99%
“…Antigen-specific T cell proliferation and IFNγ secretion was significantly higher in patients treated with sip-T compared to control patients (Kantoff et al 2010; Sheikh, et al 2013). While sip-T was approved for patients already receiving ADT, there have been two studies examining the administration of timing of ADT with sip-T. One study compared the administration of the LHRH agonist leuprolide before sip-T (ADT→sip-T) or after sip-T (sip-T→ADT) in patients with non-castrate, PSA-recurrent prostate cancer (Antonarakis, et al 2016b). PA2024-specific humoral responses were significantly elevated following sip-T treatment, although there was no difference between the two arms.…”
Section: Androgen Deprivation Combined With Immune-based Treatments –mentioning
confidence: 99%
See 1 more Smart Citation
“…The first and only approved DC vaccine is Sipuleucel-T, which targets prostatic acid phosphatase and has been shown to improve OS in patients with metastatic CRPC but showed no impact on PFS or PSA levels [58]. Sipuleucel-T combined with the androgen receptor inhibitor enzalutamide concurrently or sequentially has been investigated in patients with CRPC and results in objective radiological and PSA tumor marker responses [59]. Combination of peptide-antigen loaded DCs or intratumoral injection of immature DCs with checkpoint inhibitors have been studied and efficacy was noted in preclinical mouse models [6063].…”
Section: Introductionmentioning
confidence: 99%